IL-10(+) regulatory B cells are enriched in cord blood and may protect against cGVHD after cord blood transplantation - Sarvaria, Anushruti (Blood, 2016)
Cord blood (CB) offers a number of advantages over other sources of hematopoietic stem cells, including a lower rate of chronic graft-versus-host disease (cGVHD) in the presence of increased HLA disparity. Recent research in experimental models of autoimmunity and in patients with autoimmune or alloimmune disorders has identified a functional group of interleukin-10 (IL-10)-producing regulatory B cells (Bregs) that negatively regulate T-cell immune responses. At present, however, there is no consensus on the phenotypic signature of Bregs, and their prevalence and functional characteristics in CB remain unclear. Here, we demonstrate that CB contains an abundance of B cells with immunoregulatory function. Bregs were identified in both the naive and transitional B-cell compartments and suppressed T-cell proliferation and effector function through IL-10 production as well as cell-to-cell contact involving CTLA-4. We further show that the suppressive capacity of CB-derived Bregs can be potentiated through CD40L signaling, suggesting that inflammatory environments may induce their function. Finally, there was robust recovery of IL-10–producing Bregs in patients after CB transplantation, to higher frequencies and absolute numbers than seen in the peripheral blood of healthy donors or in patients before transplant. The reconstituting Bregs showed strong in vitro suppressive activity against allogeneic CD4(+) T cells, but were deficient in patients with cGVHD. Together, these findings identify a rich source of Bregs and suggest a protective role for CB-derived Bregs against cGVHD development in CB recipients. This advance could propel the development of Breg-based strategies to prevent or ameliorate this posttransplant complication.